A catalyst for liquid phase hydrogenation of ethylene glycol, its preparation method and application

CN118371248BActive Publication Date: 2026-10-30HAISO TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410303436.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2026-10-30
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

成型过程需要高温处理,催化剂中残留杂质多,会影响到催化剂的加氢活性

Benefits of technology

[0046]本发明的液相加氢催化剂用于乙二醇液相加氢,能大幅提高乙二醇紫外透过率,尤其是220nm、250nm、275nm的紫外透过率,提高幅度在20~60个百分点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004744934150000111
    Figure BDA0004744934150000111
  • Figure BDA0004744934150000121
    Figure BDA0004744934150000121
  • Figure HDA0004744934160000011
    Figure HDA0004744934160000011
Patent Text Reader

Abstract

The present application relates to the field of liquid phase hydrogenation, and discloses a catalyst for liquid phase hydrogenation of ethylene glycol, a preparation method and application thereof.The catalyst for liquid phase hydrogenation of ethylene glycol comprises a catalyst carrier and active components nickel and its adjuvants supported on the carrier, and the adjuvants are copper and lanthanum, wherein the nickel loading is 15-70wt%, the copper adjuvant loading is 0.25-4wt%, the lanthanum adjuvant loading is 0.25-3wt%, and the rest is the carrier.During the preparation of the catalyst, the catalyst precursor is prepared by using the parallel flow coprecipitation method with controlled reaction conditions, and after the precursor is dried and crushed, the solution of the copper and lanthanum adjuvants is sprayed during the stirring process, so that the copper and lanthanum are impregnated on the powder, thereby playing multiple roles of improving the hydrogenation activity and stability and forming pores.Compared with the prior art, the catalyst has low production cost, high hydrogenation activity and simple production process, and is used for liquid phase hydrogenation of ethylene glycol, so that the ultraviolet transmittance of ethylene glycol can be greatly improved at low pressure and low reaction temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of liquid phase hydrogenation, and in particular to a catalyst for liquid phase hydrogenation of ethylene glycol, its preparation method and application. Background Art

[0002] As a bulk chemical, more than 90% of ethylene glycol is used for polyester synthesis, and polyester has high requirements for the product quality of raw material ethylene glycol, as trace impurities may affect the performance of polyester chips; therefore, the national standard "GB / T4649-2018 Ethylene Glycol for Industrial Use" specifies 17 indicators, and polyester-grade ethylene glycol requires a purity of more than 99.9%, particularly putting forward high requirements for ultraviolet transmittance, with a transmittance at 220nm of ≥75%, a transmittance at 275nm of ≥92%, and a transmittance at 350nm of ≥99%. The ultraviolet transmittance indicators in the national standard even exceed the internationally prevalent American ASTM standard. In ASTM's E-2470-07 standard for polyester-grade ethylene glycol, the requirement for the 220nm transmittance of polyester-grade ethylene glycol is ≥70%, which is lower than the national standard requirement of ≥75%. In view of the strict national standard, it is difficult for ethylene glycol enterprises to meet the requirements only through rectification, and auxiliary treatment means are often required to make the ultraviolet transmittance of the product reach the standard.

[0003] At present, the main process is to carry out liquid phase hydrogenation on the reflux liquid of the ethylene glycol product column, then side-draw ethylene glycol is further adsorbed by ion exchange resin to remove trace impurities, so as to finally meet the standard requirements. In addition, the catalyst used for liquid phase hydrogenation is Raney nickel catalyst. On the one hand, its preparation process has high energy consumption and high price. When used in liquid materials, the nickel skeleton is prone to pulverization and loss, resulting in excessively high nickel content in the product and affecting the quality of ethylene glycol products. On the other hand, Raney nickel is prepared by activating nickel-aluminum alloy with lye, which has a small specific surface area and limited reaction activity; in the later stage of using the ethylene glycol synthesis catalyst, the impurity content in the product increases, and Raney nickel has a limited improvement effect on the ultraviolet transmittance of the reflux liquid of the ethylene glycol product column, which easily causes the ultraviolet transmittance of the product to exceed the standard. It is very necessary to develop catalysts with higher activity and greater improvement on the ultraviolet transmittance of ethylene glycol, especially for improving the product quality of ethylene glycol produced by the syngas method, which requires liquid phase hydrogenation catalysts with more excellent performance.

[0004] The impurities affecting the ultraviolet transmittance in ethylene glycol are mainly organic compounds containing unsaturated bonds, including aldehydes, ketones, esters, carboxylic acids and cyclic oxygen-containing organic compounds, etc. Through liquid phase hydrogenation, trace unsaturated organic compounds are hydrogenated into saturated organic compounds, thereby improving the ultraviolet transmittance of ethylene glycol.

[0005] Patent CN104945227B discloses a composite catalyst for ethylene glycol liquid-phase hydrogenation. It is formed by mixing carbonizable organic matter and Raney metal alloy particles, followed by high-temperature carbonization, and then leaching away soluble metal components with an alkaline solution, leaving a continuous phase of carbon and a discontinuous phase of Raney nickel. This composite catalyst has a regular shape and good activity, but requires high-temperature carbonization, has a complex preparation process, and the active material is still Raney metal nickel; the carbonized material can cover some of the reactive sites.

[0006] Patent CN111644172A discloses a sol-gel method for preparing an ethylene glycol liquid-phase hydrogenation catalyst. The active component solution is mixed with silica sol or alumina sol, and a surfactant is added. After stirring and heating, a gel is formed, which is then dried and calcined to obtain the catalyst. Before use, this catalyst requires online liquid-phase reduction, which generates wastewater. Furthermore, a certain amount of time is needed during the reaction to replace any residual reducing agent.

[0007] US patents US5536694 and US4826799 disclose methods for molding powdered Raney alloys by adding plasticizers or polymers, ultimately forming regularly shaped Raney catalysts for fixed-bed reactions. The molding process requires high-temperature treatment, resulting in numerous residual impurities in the catalyst, which can affect its hydrogenation activity. Summary of the Invention:

[0008] The technical problem to be solved by the present invention is to provide a catalyst for liquid-phase hydrogenation of ethylene glycol, its preparation method and application, which is used to address the shortcomings of the prior art. When used for liquid-phase hydrogenation of ethylene glycol, it has high activity and can significantly improve the ultraviolet transmittance of ethylene glycol.

[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution.

[0010] The first aspect of the present invention provides a catalyst for liquid-phase hydrogenation of ethylene glycol, comprising a catalyst support and an active component nickel and its additives supported on the support, wherein the additives are copper and lanthanum, wherein: the nickel loading is 15-70 wt%, preferably 30-70%, most preferably 40-60%; the copper loading is 0.25-4 wt%, preferably 1-4%, most preferably 2-3%; the lanthanum loading is 0.25-3 wt%, preferably 0.5-2%, most preferably 0.8-1.5%; and the remainder is the support.

[0011] According to the above scheme, preferably, the nickel loading is 30-70%, most preferably 40-60%, the copper loading is 1-4%, most preferably 2-3%, the lanthanum loading is 0.5-2%, most preferably 0.8-1.5%, and the remainder is a carrier.

[0012] According to the above scheme, preferably, the specific surface area of ​​the catalyst of the present invention is 80-400 m². 2 / g, average pore size 5-18nm, pore volume 0.5-1.5ml / g.

[0013] According to the above scheme, preferably, the nickel grain size is 3-9 nm.

[0014] According to the above scheme, the catalyst support is alumina, silicon oxide, or a silicon-alumina composite support, preferably alumina.

[0015] According to the above scheme, the catalyst is obtained by adding an aqueous solution containing copper and lanthanum to a co-precipitated aluminum and / or silicon precursor and a nickel precursor, granulating, drying, calcining, and pressing into tablets.

[0016] The second aspect of this invention provides a method for preparing an ethylene glycol liquid-phase hydrogenation catalyst. The method involves using a mixed aqueous solution of aluminum nitrate and / or alkaline silica sol, nickel nitrate, and anhydrous sodium carbonate aqueous solution, and obtaining a uniformly dispersed suspension via co-precipitation. The suspension is then aged at room temperature to obtain a filter cake. The filter cake is processed to obtain a catalyst precursor. The precursor is pulverized into powder. A mixed aqueous solution of copper nitrate and lanthanum nitrate is sprayed onto the powder during powder stirring. After thorough stirring, the powder is granulated using a granulator. The granulated powder is then dried, calcined at 350–650°C for 2–8 hours, cooled to room temperature, and then tableted using a tablet press to obtain the catalyst.

[0017] According to the above scheme, the silica content of the alkaline silica sol is between 10% and 35%.

[0018] According to the above scheme, the particle size of the powder after the precursor is crushed is 40-200 mesh.

[0019] According to the above scheme, cylindrical catalysts are prepared by compression. The diameter of the cylindrical catalyst is 3-6 mm, the height of the column is 3-6 mm, and the side pressure strength of the catalyst is 50-200 N / cm.

[0020] The silicon-to-aluminum ratio of the silicon-aluminum composite support does not affect the liquid-phase hydrogenation effect of the catalyst, but the specific surface area of ​​the silicon-aluminum composite support decreases relative to that of alumina as the silicon oxide content increases. Considering the economics of catalyst production, alumina is preferred as the support.

[0021] According to the above scheme, when using alumina as a carrier, the nickel-aluminum molar ratio in the nickel nitrate and aluminum nitrate mixed solution is between 0.3:1 and 5.2:1.

[0022] According to the above scheme, the temperature of the mixed aqueous solution of aluminum nitrate and / or alkaline silica sol and nickel nitrate is between 40 and 80°C, and the temperature of the anhydrous sodium carbonate solution is between 40 and 80°C.

[0023] According to the above scheme, in the co-precipitation method, the concentration of the aqueous solution of aluminum nitrate and / or alkaline silica sol is 0.1-2 mol / L, the concentration of the aqueous solution of nickel nitrate is 0.1-2 mol / L, and the concentration of the aqueous solution of anhydrous sodium carbonate is 0.5-2.5 mol / L.

[0024] According to the above scheme, during co-precipitation, the flow rates of the two solutions are the same, between 0.1 and 25 L / min. Deionized water is added to the stirred tank in advance to a level of 5 to 10%. The mixture is stirred at a constant speed for 2 to 6 hours, with the stirring speed between 10 and 200 rpm. The pH of the solution is maintained between 7.5 and 8.5, and the temperature of the solution is maintained between 40 and 80°C during the stirring process.

[0025] According to the above scheme, the filter cake is aged at room temperature for 2 to 20 hours, filtered or centrifuged to obtain a fine filter cake; the filter cake is washed with deionized water 2 to 10 times and dried to obtain the catalyst precursor.

[0026] According to the above scheme, the concentration of copper nitrate or lanthanum nitrate in the mixed aqueous solution of copper nitrate and lanthanum nitrate is 0.1-2 mol / L. The solution is added to the mixed solution at a weight ratio of 10-25% of the precursor powder weight. During the powder stirring process, the solution is evenly sprayed into the powder. After thorough stirring, the powder is granulated on a granulator.

[0027] According to the above scheme, the particle size of the catalyst powder obtained by granulation is between 10 and 100 mesh.

[0028] According to the above scheme, the specific steps for preparing an ethylene glycol liquid-phase hydrogenation catalyst using aluminum nitrate and / or alkaline silica sol as precursor sources and supported by alumina, silica, or a silica-alumina composite are as follows:

[0029] (1) Prepare a mixed aqueous solution of aluminum nitrate and / or alkaline silica sol and nickel nitrate with a concentration of 0.1 to 2 mol / L, stir and dissolve at room temperature, and heat; prepare an aqueous solution of anhydrous sodium carbonate with a concentration of 0.5 to 2.5 mol / L, and heat.

[0030] (2) Add the two solutions to the stirred tank at the same flow rate. Add 5-10% deionized water to the stirred tank in advance, stir at a constant speed for 2-6 hours at a speed of 10-200 rpm, and maintain the pH of the solution between 7.5 and 8.5.

[0031] (3) After stirring stops, a uniformly dispersed suspension is formed. The suspension is allowed to stand at room temperature for 2 to 20 hours. The mixture is then filtered or centrifuged to obtain a fine filter cake.

[0032] (4) Wash the filter cake with deionized water 2 to 10 times, dry it, and obtain the catalyst precursor;

[0033] (5) The precursor is crushed into powder;

[0034] (6) Prepare a mixed aqueous solution of copper nitrate and lanthanum nitrate of 0.1-2 mol / L, add the mixed solution at a weight ratio of 10-25% of the precursor powder weight, spray the solution evenly into the powder during the powder stirring process, and granulate it on a granulator after thorough stirring.

[0035] (7) After granulation, the powder is dried again, calcined at 350-650℃ for 2-8 hours, cooled to room temperature, and then tableted on a tablet press to obtain the catalyst.

[0036] According to the above scheme, the drying in step (4) or (7) is performed at 120°C for 4 to 12 hours.

[0037] According to the above scheme, in the nickel nitrate and aluminum nitrate mixed solution, the nickel-aluminum molar ratio is between 0.3:1 and 5.2:1, the temperature of the mixed solution is between 40 and 80℃, and the temperature of the anhydrous sodium carbonate solution is between 40 and 80℃. During co-precipitation, the flow rates of the two solutions are the same, between 0.1 and 25 L / min, and the stirring speed of the stirred tank is between 10 and 200 rpm. When stirring at a constant speed in the stirred tank, 5-10% of the solution level of deionized water is added in advance, and the solution temperature is maintained between 40 and 80℃ during the stirring process.

[0038] A third aspect of the present invention provides a method for liquid-phase hydrogenation purification of ethylene glycol using the above-mentioned catalyst for liquid-phase hydrogenation, wherein the ethylene glycol material is hydrogenated to improve the ultraviolet transmittance of ethylene glycol.

[0039] According to the above scheme, the UV transmittance of ethylene glycol treated by the above method is significantly improved. Compared with the UV transmittance of imported liquid ethylene glycol, the UV transmittance at 220nm can be increased by more than 25 percentage points, more preferably by more than 30 percentage points, and the UV transmittance at 250nm and 275nm can be increased by more than 35 percentage points, more preferably by more than 45 percentage points, and optimally by more than 50 or even 60 percentage points.

[0040] According to the above scheme, the hydrogenation can be performed on the reflux liquid of the distillation product column, or on the side stream of the product column and the top stream of the ethylene glycol recovery column. The hydrogenation materials include the reflux liquid of the product column in ethylene glycol distillation, the recovered material of the recovery column, and the side stream of the product column, etc. The impurities in the hydrogenation materials are hydrogenated to improve the ultraviolet transmittance of ethylene glycol.

[0041] This invention utilizes a hydrogenation catalyst formed by nickel, copper, and lanthanum. Nickel exhibits strong hydrogen adsorption capacity and a high hydrogenation saturation ability for aldehydes, ketones, and esters. Copper has a strong hydrogenation saturation ability for esters. Lanthanum itself has a relatively weak hydrogen adsorption capacity, and lanthanum atoms are much larger than nickel and copper atoms. The combination of lanthanum with nickel and copper prevents the aggregation of nickel and copper atoms on the support surface, thus preventing the growth or agglomeration of nickel and copper grains. This improves and maintains the hydrogenation activity of the catalyst, resulting in a stable and excellent hydrogenation capacity. Furthermore, by adding copper as an additive during the granulation process, copper is mainly distributed on the outer surface of the support or near the micropore inlet, fully leveraging its strong ester adsorption capacity. Due to the presence of nickel, the catalyst surface has a high hydrogen adsorption concentration, making it easier for copper to saturate the adsorbed esters. The synergistic effect of these two metals enhances the catalyst's hydrogenation activity for esters, particularly beneficial for the hydrogenation of esters in ethylene glycol.

[0042] In the preparation of the catalyst of this invention, a co-precipitation method with controlled reaction conditions is used to prepare the catalyst precursor. After the precursor is dried and pulverized, a solution of copper and lanthanum additives is sprayed during stirring, allowing the copper and lanthanum to impregnate the powder. Granulation and tableting are then performed, which improves the hydrogenation activity and stability, while simultaneously achieving multiple functions such as tableting and pore formation. Granulation before tableting improves the flowability of the powder, ensuring stable feeding and uniform tablet strength. Subsequent tableting helps control the porosity and specific surface area after tableting. Furthermore, wet granulation using the additive solution allows for efficient dispersion of the additives on the catalyst reaction surface, enabling the additives to fully exert their effects and inhibiting the growth of nickel grains, synergistically improving hydrogenation activity and stability. Preferably, the specific surface area of ​​the catalyst of this invention is 80–400 m². 2 / g, average pore size 5-18nm, pore volume 0.5-1.5ml / g. Nickel particle size can be controlled within 3-9nm.

[0043] This catalyst is used for the hydrogenation of ethylene glycol. When unsaturated organic compounds in liquid ethylene glycol are adsorbed onto the catalyst surface, the adsorbed hydrogen and the unsaturated organic compounds undergo a hydrogenation reaction, transforming the unsaturated organic compounds into saturated organic compounds. The carbon-oxygen double bond of the carbonyl group is hydrogenated to a carbon-oxygen single bond, thereby converting aldehydes, ketones, and esters into alcohols without double bonds. The content of double-bonded organic compounds in ethylene glycol is reduced, the absorption of ultraviolet light is reduced, and the ultraviolet transmittance of ethylene glycol is improved.

[0044] This patented catalyst undergoes gas-phase reduction before use, and is then stored in deionized water. When needed, it is loaded into a liquid-phase hydrogenation reactor, and after purging the system with nitrogen or hydrogen, it is ready for use. When applied to the liquid-phase hydrogenation of reflux liquid from ethylene glycol distillation products or materials from ethylene glycol recovery towers, this catalyst significantly improves UV transmittance compared to Raney nickel catalysts. When applied to the liquid-phase hydrogenation of ethylene glycol side-products, it can directly increase the UV transmittance of ethylene glycol to polymerization-grade levels, eliminating the need for ion exchange resin adsorption before the product enters the storage tank, simplifying the production process, and reducing production costs.

[0045] The beneficial effects of this invention are:

[0046] The liquid-phase hydrogenation catalyst of the present invention can be used for liquid-phase hydrogenation of ethylene glycol, which can significantly improve the ultraviolet transmittance of ethylene glycol, especially the ultraviolet transmittance at 220nm, 250nm and 275nm, with an increase of 20 to 60 percentage points.

[0047] Compared with industrially used Raney nickel catalysts, the liquid-phase hydrogenation catalyst of this invention has a regular catalyst structure, is easy to pack, has high hydrogenation activity for impurities in ethylene glycol, and significantly improves the ultraviolet transmittance of ethylene glycol; the catalyst has low production cost, simple production process, and low energy consumption. Attached Figure Description

[0048] Figure 1 The UV transmittance of the material at 220nm is used for lifetime testing. Detailed Implementation

[0049] The present invention will be further described in detail below with reference to embodiments, but this does not limit the present invention.

[0050] Example 1:

[0051] (1) Weigh 71.5g of nickel nitrate with 6 molecules of water of crystallization and 106g of aluminum nitrate with 9 molecules of water of crystallization, and dissolve them together in 500ml of deionized water. Weigh 106g of anhydrous sodium carbonate and dissolve it in 600ml of deionized water. Heat the dissolved salt solution in a water bath to between 40-80℃.

[0052] (2) Add 200g of water to a 2L beaker and place it in a water bath between 40-80℃. Stir at 20rpm using a magnetic stirrer while simultaneously adding nitrate solution and anhydrous sodium carbonate solution at a flow rate of 80ml / min. After the solution has been completely added, continue stirring for 2 hours. After stopping stirring, allow it to cool naturally to room temperature and allow it to age for 4 hours.

[0053] (3) Centrifuge the aged emulsion suspension and wash it 5 times with deionized water.

[0054] (4) Bake the filter cake at 120℃ for 6 hours.

[0055] (5) Crush the block filter cake in a pulverizer for 2 minutes to obtain powder with a particle size of 40-200 mesh;

[0056] (6) Weigh 3.3g of copper nitrate with 3 water of crystallization and 0.9g of lanthanum nitrate with 6 water of crystallization, prepare a mixed aqueous solution of 13g, spray the solution onto the dry precursor powder, stir the powder thoroughly, and granulate it on a granulator.

[0057] (7) After granulation, the particle size of the powder is between 10-100 mesh. It is dried at 120℃ for 4 hours and calcined at 400℃ for 4 hours.

[0058] (8) Press into tablets on a tablet press. The particles have an average strength of 150 N / cm.

[0059] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The ultraviolet transmittance was measured at the feed and outlet. The measurement data are shown in Table 1, Example 1.

[0060] Comparative Example 1:

[0061] (1) Weigh 71.5g of nickel nitrate with 6 molecules of water of crystallization, 106g of aluminum nitrate with 9 molecules of water of crystallization, 3.3g of copper nitrate with 3 molecules of water of crystallization, and 0.9g of lanthanum nitrate with 6 molecules of water of crystallization, and dissolve them together in 500ml of deionized water. Weigh 106g of anhydrous sodium carbonate and dissolve it in 600ml of deionized water. Heat the dissolved salt solution in a water bath to between 40-80℃.

[0062] (2) Add 200g of water to a 2L beaker and stir at 20rpm on a magnetic stirrer. Simultaneously add nitrate solution and anhydrous sodium carbonate solution at a flow rate of 80ml / min while stirring. After the solution has been completely added, continue stirring for 2 hours. After stopping stirring, allow it to cool naturally and place it at room temperature for 4 hours of static aging.

[0063] (3) Centrifuge the aged emulsion suspension and wash it 5 times with deionized water.

[0064] (4) Bake the filter cake at 120℃ for 6 hours.

[0065] (5) Crush the block filter cake in a pulverizer for 2 minutes to obtain powder with a particle size of 40-200 mesh;

[0066] (6) Weigh 13g of deionized water, spray the solution onto the dry precursor powder, stir the powder thoroughly, and granulate it on a granulator.

[0067] (7) After granulation, the particle size of the powder is between 10-100 mesh. It is dried at 120℃ for 4 hours and calcined at 400℃ for 4 hours.

[0068] (8) Press into tablets on a tablet press. The particles have an average strength of 150 N / cm.

[0069] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The UV transmittance was measured at the feed and outlet. This preparation method involves co-dissolving four nitrates and then co-precipitating them. The resulting catalyst exhibits significantly lower hydrogenation activity for impurities in ethylene glycol compared to the catalyst in Example 1. Experimental data under the same conditions are shown in Table 1 (Example 1).

[0070] Example 2:

[0071] (1) Weigh 105.5g of nickel nitrate with 6 molecules of water of crystallization and 106g of aluminum nitrate with 9 molecules of water of crystallization, and dissolve them together in 500ml of deionized water. Weigh 124g of anhydrous sodium carbonate and dissolve it in 600ml of deionized water. Heat the dissolved salt solution in a water bath to between 40-80℃.

[0072] Steps (2) to (5) are the same as steps (2) to (5) in Example 1;

[0073] (6) Weigh 4g of copper nitrate with 3 water of crystallization and 1.1g of lanthanum nitrate with 6 water of crystallization, prepare a mixed aqueous solution of 16g, spray the solution onto the dry precursor powder, stir the powder thoroughly, and granulate it on a granulator.

[0074] Steps (7) and (8) are the same as steps (7) and (8) in Example 1;

[0075] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The ultraviolet transmittance was measured at the feed and outlet. The measurement data are shown in Example 2 in Table 1.

[0076] Comparative Example 2

[0077] (1) Weigh 105.5g of nickel nitrate with 6 molecules of water of crystallization and 106g of aluminum nitrate with 9 molecules of water of crystallization, and dissolve them together in 500ml of deionized water. Weigh 106g of anhydrous sodium carbonate and dissolve it in 600ml of deionized water. Heat the dissolved salt solution in a water bath to between 40-80℃.

[0078] Steps (2) to (5) are the same as steps (2) to (5) of Comparative Example 1;

[0079] (6) Weigh 16g of deionized water, spray the solution onto the dry precursor powder, stir the powder thoroughly, and granulate it on a granulator.

[0080] Steps (7) and (8) are the same as steps (7) and (8) of Comparative Example 1;

[0081] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The UV transmittance was measured at the feed and outlet. In this preparation method, no copper or lanthanum additives were added during the co-precipitation process. The resulting catalyst showed significantly lower hydrogenation activity against impurities in ethylene glycol compared to the catalysts in Examples 1 and 2, indicating that the catalyst with additives added during granulation exhibited better hydrogenation activity. The catalysts prepared by simultaneous precipitation of additives and active components (Comparative Example 1) or without additives (Comparative Example 2) showed lower catalyst activity than the method implemented in this patent. Experimental data under the same conditions are shown in Table 1 (Comparative Example 2).

[0082] Example 3:

[0083] (1) Weigh 71.5g of nickel nitrate with 6 molecules of water of crystallization and 106g of aluminum nitrate with 9 molecules of water of crystallization, and dissolve them together in 500ml of deionized water. Weigh 106g of anhydrous sodium carbonate and dissolve it in 600ml of deionized water. Heat the dissolved salt solution in a water bath to between 40-80℃.

[0084] Steps (2) to (5) are the same as steps (2) to (5) in Example 1;

[0085] (6) Weigh 2.2g of copper nitrate with 3 water of crystallization and 1.8g of lanthanum nitrate with 6 water of crystallization, prepare a mixed aqueous solution of 13g, spray the solution onto the dry precursor powder, stir the powder thoroughly, and granulate it on a granulator.

[0086] Steps (7) and (8) are the same as steps (7) and (8) in Example 1;

[0087] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The ultraviolet transmittance was measured at the feed and outlet. In Example 3, the additive content was adjusted compared to Example 1. Within the range shown in the patent, the catalyst hydrogenation activity was unaffected. Measurement data are shown in Table 1 for Example 3.

[0088] Example 4:

[0089] Steps (1) to (7) are the same as (1) to (7) in Example 1.

[0090] (8) Press into tablets on a tablet press. The particles have an average strength of 150 N / cm.

[0091] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The ultraviolet transmittance was measured at the feed and outlet. In Example 4, the catalyst tablet diameter and height changed compared to Example 1, but the hydrogenation activity remained basically unchanged. The measurement data are shown in Table 1, Example 4.

[0092] Example 5:

[0093] Steps (1) to (7) are the same as (1) to (7) in Example 1.

[0094] (8) Press into tablets on a tablet press. The particles have an average strength of 200 N / cm.

[0095] (9) 30 ml of catalyst is loaded into a fixed-bed reactor and reduced using pure H2 or hydrogen / nitrogen gas. The maximum reduction temperature is 400℃, and the reduction time is 4-8 h. The temperature is then lowered to 100℃, using the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with a liquid hourly space velocity (LHSV) of 2.5 h⁻¹. -1 The UV transmittance was measured at the feed and outlet. In Example 5, compared to Example 1, the average strength of the catalyst tablet was increased, and the hydrogenation activity was slightly reduced within the range shown in the patent, but the change was not significant. The measurement data are shown in Table 1, Example 5.

[0096] Comparative Example 3:

[0097] (1) Under the protection of deionized water, 30 ml of Raney nickel catalyst used in a certain ethylene glycol plant was loaded into a fixed bed reactor.

[0098] (2) Heat the reactor to 110°C with pure H2, replace the water in the reactor with nitrogen or hydrogen, and then cool it to 100°C. Use the reflux liquid from the ethylene glycol product tower as the inlet feedstock, with an LHSV of 2.5h. -1 The UV transmittance was measured at the feed and outlet. The measurement data are shown in Table 1, Example 3.

[0099] Table 1. Changes in UV transmittance of ethylene glycol after liquid-phase hydrogenation.

[0100]

[0101]

[0102] The above indicates that the catalyst of the present invention can significantly improve the ultraviolet transmittance of ethylene glycol, has a strong ability to hydrogenate impurities in ethylene glycol, and its effect on improving the ultraviolet transmittance of ethylene glycol products is far greater than that of traditional Raney nickel catalysts. When applied to industrial production, it can simplify the production process and greatly improve product quality.

[0103] The liquid-phase hydrogenation catalyst of the present invention is prepared according to the preparation method of the present invention. The particles have an average strength of 156 N / cm and contain 45% nickel, 2.2% copper, and 0.9% lanthanum. This catalyst was used for the liquid-phase hydrogenation of ethylene glycol. Laboratory stability tests were conducted for 6 days under the following conditions: pure H2 atmosphere, pressure 0.5 MPa, temperature 110℃, and LHSV = 2.4 h. -1 The reflux feed from the ethylene glycol product tower had an inlet 220nm UV transmittance of 1.3% and an inlet aldehyde content of 49.8 ppm. The H2 flow rate was maintained at 10-100 ml / min. Results showed that the liquid-phase hydrogenation catalyst of this invention significantly improved the hydrogenation removal efficiency of aldehydes, ketones, and esters in ethylene glycol liquid-phase hydrogenation. Taking aldehydes as an example, the inlet aldehyde content was 49.8 ppm, and the outlet aldehyde content was 6-6.5 ppm, with a removal rate greater than 86%. It also significantly improved the UV transmittance of ethylene glycol. Taking the 220nm UV transmittance as an example, the outlet 220nm UV transmittance remained stable above 25%, an increase of 23.7 percentage points compared to the inlet's 1.3%. The 220nm transmittance of the outlet feed in the lifetime test is shown below. Figure 1 .

Claims

1. A catalyst for the liquid-phase hydrogenation of ethylene glycol, characterized in that: The catalyst includes a catalyst support and an active component, nickel, and its additives loaded on the support. The additives are copper and lanthanum. The catalyst support is alumina, silica, or a silica-alumina composite support. The nickel loading is 15-70 wt%, the copper loading is 0.25-4 wt%, the lanthanum loading is 0.25-3 wt%, and the remainder is the support. The catalyst is obtained by granulating, drying, calcining, and pressing a co-precipitated catalyst precursor containing aluminum and / or silicon and nickel into tablets with an aqueous solution containing copper and lanthanum.

2. The catalyst for liquid-phase hydrogenation of ethylene glycol according to claim 1, characterized in that: The nickel loading is 30~70wt%, the copper loading is 1~4wt%, the lanthanum loading is 0.5~2wt%, and the remainder is catalyst support.

3. The method for preparing the catalyst for liquid-phase hydrogenation of ethylene glycol according to claim 1, characterized in that: A uniformly dispersed suspension was obtained by co-precipitation using a mixed aqueous solution of aluminum nitrate and / or alkaline silica sol, nickel nitrate, and anhydrous sodium carbonate. The suspension was then aged at room temperature to obtain a filter cake. The filter cake was then processed to obtain a catalyst precursor containing aluminum and / or silicon and nickel. The catalyst precursor was pulverized into powder. During the powder stirring process, a mixed aqueous solution of copper nitrate and lanthanum nitrate was sprayed onto the powder. After thorough stirring, the powder was granulated on a granulator. The granulated powder was dried, calcined at 350~650℃ for 2~8h, cooled to room temperature, and then tableted on a tablet press to obtain a catalyst for the liquid-phase hydrogenation of ethylene glycol.

4. The preparation method according to claim 3, characterized in that: The particle size of the pulverized catalyst precursor is 40-200 mesh; the particle size of the granulated catalyst powder is between 10-100 mesh; the cylindrical catalyst is prepared by tableting, with a diameter of 3-6 mm, a column height of 3-6 mm, and a side pressure strength of 50-200 N / cm.

5. The preparation method according to claim 3, characterized in that: When using alumina as a carrier, the nickel-aluminum molar ratio in a mixed solution of nickel nitrate and aluminum nitrate is between 0.3:1 and 5.2:

1.

6. The preparation method according to claim 3, characterized in that: In the co-precipitation method, the concentration of the aqueous solution of aluminum nitrate and / or alkaline silica sol is 0.1~2 mol / L, the concentration of the aqueous solution of nickel nitrate is 0.1~2 mol / L, and the concentration of the aqueous solution of anhydrous sodium carbonate is 0.5~2.5 mol / L. During coprecipitation, the flow rates of the two solutions are the same, between 0.1~25 L / min. Deionized water is added to the stirred tank in advance to a level of 5~10%, and the mixture is stirred at a constant speed for 2~6 h. The stirring speed of the stirred tank is between 10~200 rpm, the pH of the solution is maintained between 7.5~8.5, and the temperature of the solution is maintained between 40~80℃ during the stirring process.

7. The preparation method according to claim 3, characterized in that: The concentration of copper nitrate or lanthanum nitrate in the mixed aqueous solution of copper nitrate and lanthanum nitrate is 0.1~2 mol / L. The solution is added to the mixed solution at a weight ratio of 10~25% of the precursor powder weight. During the powder stirring process, the solution is evenly sprayed into the powder. After thorough stirring, the powder is granulated on a granulator.

8. A method for liquid-phase hydrogenation purification of ethylene glycol using the catalyst according to claim 1, characterized in that: The catalyst described in claim 1 is used to catalytically hydrogenate ethylene glycol materials, thereby improving the ultraviolet transmittance of ethylene glycol.

9. The method according to claim 8, characterized in that: The UV transmittance of the treated ethylene glycol is significantly improved. Compared with the imported UV transmittance, the 220nm UV transmittance is increased by more than 25 percentage points, and the 250nm and 275nm UV transmittance are increased by more than 35 percentage points.

Citation Information

Patent Citations

  • A method for hydrorefining of ethylene glycol

    CN104945227B

  • Pressure plate for

    US247007A

  • Shaped catalyst and process for making it

    US4826799A

  • Catalyst precursor for an activated raney metal fixed-bed catalyst, an activated raney metal fixed-bed catalyst and a process for its preparation and use, and a method of hydrogenating organic compounds using said catalyst

    US5536694A

  • Nickel system hydrogenation catalyst, preparation method and application

    CN101037613A